2023
DOI: 10.3390/educsci13070639
|View full text |Cite
|
Sign up to set email alerts
|

VR Gaming for Meta-Skills Training in Special Education: The Role of Metacognition, Motivations, and Emotional Intelligence

Abstract: Inclusion, equality, and well-being for all, especially for people with special needs and disabilities, is globally recognized as a priority. At the same time, there is an urgent need to create digital training environments for people with special educational needs and disabilities (SEND). Virtual reality (VR) and gaming technologies have entered the race at full speed for skills training. Despite significant research on each of these technologies, there is still limited knowledge about the effectiveness of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 119 publications
0
16
0
Order By: Relevance
“…Presence may mirror similar components as that of restoration ( Lessiter et al, 2001 ; Schubert et al, 2001 ; Freeman, 2004 ; De Kort et al, 2006 ). According to Mitsea et al (2023) , VR content minimizes cognitive load, mental fatigue, and increases processing capacity. Several studies have shown that fun ratings for VR positively correlate with sense of presence and pain reduction ( Hoffman et al, 2006 , 2008 ; Maani et al, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Presence may mirror similar components as that of restoration ( Lessiter et al, 2001 ; Schubert et al, 2001 ; Freeman, 2004 ; De Kort et al, 2006 ). According to Mitsea et al (2023) , VR content minimizes cognitive load, mental fatigue, and increases processing capacity. Several studies have shown that fun ratings for VR positively correlate with sense of presence and pain reduction ( Hoffman et al, 2006 , 2008 ; Maani et al, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…VR content may not only distract a user’s attention but also direct the user’s attention toward targeted goals or behaviors ( Mitsea et al, 2023 ). Digital game-based tasks that challenge the user to overcome obstacles through attention or observation offer intrinsic or external rewards and reinforcement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Because VR provides a ludic, safe, controlled, and motivating training environment, it can be an interesting avenue of intervention for people with several types of disabilities. VR educational applications have already demonstrated promising results in this regard (Mitsea et al, 2023).…”
Section: Introductionmentioning
confidence: 99%